Addition of TyG index to the GRACE score improves prediction of adverse cardiovascular outcomes in patients with non-ST-segment elevation acute coronary syndrome undergoing percutaneous coronary intervention: A retrospective study - Pang, Shuo; Miao, Guangrui; Zhou, Yuanhang; Du, Yang; Rui, Ziao; Zhao, Xiaoyan (Frontiers in Cardiovascular Medicine, 2022)
Background: The Global Registry of Acute Coronary Events (GRACE) score is a widely recognized method for predicting adverse cardiovascular events in patients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS). The triglyceride-glucose index (TyG index) is a new biomarker of insulin resistance and has been proven to be closely related to the occurrence of adverse cardiovascular events. We investigated whether the addition of the TyG index to the GRACE score could improve prognosis prediction in patients with NSTE-ACS undergoing percutaneous coronary intervention (PCI). Methods: In total, 515 patients with NSTE-ACS undergoing PCI were included in this retrospective study. The incidence of primary endpoint events was compared between TyG+GRACE and GRACE alone using Kaplan-Meier curves. The relationship between the TyG index and GRACE score was analyzed using Spearman’s rank correlation. Univariate and multivariate Cox proportional hazards analyses were used to identify independent risk factors. Based on the receiver operating characteristic curve, net reclassification improvement (NRI), integrated differentiation improvement (IDI), and decision curve analysis, the TyG index was evaluated for its predictive value when added to the GRACE score. Results: The TyG index was an independent predictor of 2-year adverse cardiovascular events in patients with NSTE-ACS undergoing PCI. The combination of the TyG index with the GRACE score can improve the ability of the GRACE score alone to predict 2-year adverse cardiovascular events compared with the GRACE score alone (area under the curve (AUC)= 0.849, P =0.043; NRI=0.718, P < 0.001; IDI=0.086, P<0.001). Conclusion: Combining the TyG index and GRACE score could improve the prediction of the occurrence of 2-year adverse cardiovascular events. This new risk model has important clinical applications.